(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This is a first study which looked at the specific examples of government expenditure on well-being and related territories in India in the past and connected them to the tracking of well-being outcomes. First, average rates of direct policy expenditure on well-being, family government support and infant welfare are foolishly small by international metrics, per individual, as well as a share of GDP. Government spending on well-being contributes to less than 1 per cent of GDP. This has indicated that households in India account for a disproportionately high and rising share of the weight of public resources, to the degree that they account for an increasing share of overall spending (nearly seventy-five per cent of the last year for which evidence is available). Like many countries, this is basically about cash-based prices, which are inherently backward. In comparison, the share of family unit spending expenditure on human services has also risen over a period of time, especially in regional areas where it currently accounts for almost 7 per cent of the family financial program in large part.